Cali, Colombia, Key learning City C/Can 2025: City Cancer Challenge (Colombia Medica, 2017)
Cali (Colombia) will be the first city in the world to implement the initiative “C/Can 2025: City Cancer Challenge”1 (http://www.uicc.org/what-we-do/convening/ccan-2025-city-cancer-challenge). With 2.4 million inhabitants, Cali is the second-largest city of Colombia and a key urban focal point for the immigration of the country’s rural population which represents one fifth of Colombia’s 45.5 million inhabitants.